SUPPORT MARITIME CONNECTIVITY TO POTENTIAL RESOURCES IN SUMATERA ISLAND - alhamidi alhamidi; Pradono Pradono; M. Zainal Ibad (Puslitbang Transportasi Antarmoda-Kementerian Perhubungan Republik Indonesia, 2020)
The development of Sumatera provides national economic progress of Sumatera role by thirty-one percent. The role of Sumatera against constellation of national economies is not separated from commodity potential and maritime transport support as catalyzation in stimulating the growth of regional economic sectors such as industry, trade and tourism. However, not yet significant impact is felt, the strengthening of commodity distribution connectivity is necessary. This research aims to know the support of maritime connectivity Sumatera port to potential commodity in Sumatera. Methodology is a method of policy analysis, commodity productivity, spatial and maritime connectivity index. The results showed that there were thirty-two nodes of commodity development supported by maritime transport with the magnitude of maritime connectivity and the movement of goods in-out the territory of Sumatera in the constellation Sumatera/national/international showed the high role of one maritime transport through Tanjung Uban port (47.34 million tons), Dumai port (12.16 million tons) and Boom Baru port (7.6 million tons). The support of movement of commodity goods increases wheels of the economy and suppresses the disparities of Sumatera Region